Penegakan Hukum Terhadap Money Politic Pada Pemilihan Legislatif Kota Pekalongan Tahun 2019 - Khusnul Khotimah; Jumailah (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research examines Law Enforcement Against Money Politics in the 2019 Pekalongan City Legislative Election. In Pekalongan City there were two cases of money politics, which the Bawaslu carried out law enforcement, but the law enforcement was not optimal. Law enforcement was carried out against the defendant FK up to the court level and he was found guilty of practicing money politics. naHowever, the defendant FK filed an appeal which stated that the defendant FK was not legally and convincingly proven guilty of committing the crime as charged. Meanwhile, law enforcement against the FM Candidate case was declared not to meet the material requirements, so the process of handling election crimes was stopped. The legal consequence of the lack of maximum law enforcement against money politics that has been carried out by the Sentra Gakkumdu Pekalongan team is that the legal culture and legal substance are not optimal as a sub-system of the overall election crime, which then gives rise to corrupt legislative candidates. Unfinished cases of money politics violations can lead to weak rules that must be enforced regarding regulations on money politics in elections, because money politics can damage the quality of election organizers and damage the quality of the leaders they produce.